Polarization-interference mapping of networks in diffusal polycristaline biological tissues (Bìofìzičnij vìsnik (Online), 2019)
Objectives: Development and experimental testing of the complex of Stokes-polarimetry and interferometry methods using algorithms for digital holographic reconstruction of the amplitude-phase structure of object fields for obtaining interrelationships between 3D distributions of depolarization maps and peculiarities of the polycrystalline structure of histological sections of biological tissues of different morphological structures and physiological state. Materials and methods: The basis of the 3D Müller-matrix mapping method is the use of a reference wave of laser radiation, which is superimposed on a polarization-non-uniform image of the biological layer in the scheme of the optical interferometer. Results: In the process of comparative analysis of the map of depolarization of biological tissues with different geometric scales of the morphological structure, we found different rates of growth of the degree of depolarization.